Back to Orthoepia – Spelling in Pronunciation Instruction: “Words Commonly Mispronounced” by Learners of Six L1s - Nowacka, Marta A. (Research in Language, 2018)
This is a continuation of Nowacka’s (2016) study on the importance of local and global errors and spelling in pronunciation instruction. Unlike in the previous research that focused on the performance of Polish learners only, respondents of six different nationalities are included, in search of some cross-national universals or absence of them. This study seeks to answer the following questions: whether there is a need to focus on spelling in a pronunciation course with learners representing six different L1s and if this is the case which graphophonemic / phonotactic rules of English should be explicitly taught to all of these learners and which ones might be L1 specific only. The intention is also to empirically confirm the existence of local errors in the performance of around 240 speakers and 50 more listeners, constituting 291 listeners of six nationalities (Kazakh, Malaysian, Polish, Turkish, Tajik and Ukrainian) and to confirm the usefulness of memorizing Sobkowiak’s (1996) ‘Words Commonly Mispronounced’ even for learners of different L1s.